IMPLEMENTATION OF MODEL BASED LEARNING THROUGH MULTIMEDIA CONTENT IN WHICH APPLY TO GIVE AND RECIEVE CONTRASTIVITY VERB IN JAPANESE AND INDONESIAN - Ariani Tanjung (JURNAL ARBITRER, 2015)
Contrastive is a study that is focused on the field of phonetics, vocabulary, grammar, etc. between two or more languages with linguistic that differentiates various activities to gain clarity on the part of the symmetric and asymmetric. In the Japanese language, the verb “memberi” and “menerima”are part of Jujudoshi verbs, which consist of 5 words to “memberi” and 2 words to menerima” whose use has tiers or in polite form (Keigo), while in Indonesian, they are only represented by “memberi” and “menerima” that have no level or in the polite form. In the Japanese, the process of “memberi” and “menerima” take the position/status of subject and object, but in Japanese, there is no level the level or in other words they do rot depend on the position or status of the subject and the cbject . The “memberi” and “menerima” words in Japanese have been already formed, whereas in Indonesian language, they are derived by adding suffixes. In terms of function, “memberi” and “menerima” in Japanese and Indonesian languages have similarities, which discloses a process of giving and taking subject and object, which subject always get benefit from the process. In terms of the meaning, “memberi” and “menerima’ are represent semantic actions, and circumstances.